Efecto de la inclusión en diferentes niveles de lignocelulosa sobre los parámetros digestivos en cobayos (Cavia porcellus) - Bastidas Carrión, Josselyn Lisseth (2024)
The guinea pig is a monogastric herbivore with a simple stomach, through whichfood passes speedily. The objective of the present investigation was to determine the effect of the inclusion of different levels of lignocellulose on the digestive parameters of guinea pigs (Cavia porcellus). Thirty-two animals weaned at 15 days of age, 50% females and 50% males, were assigned to a 4x2 factorial arrangement, diets by sex, organized in a completely randomized design. The guinea pigs were randomly divided into four treatments with the inclusion of 0, 3, 3, 8, 12% lignocellulose, with 8 replicates per treatment. The variables studied were absolute and relative weight of the digestive organs, absolute and relative length of the small intestine and stomach and cecal pH. The results were subjected to analysis of variance (ANOVA) and protected T-test for comparison of means. Statistical difference was observed in absolute weight of stomach 29.7 g (p ≤ 0.033) with 0% inclusion of lignocellulose and small intestine with 33.4 g (p ≤ 0.043) in females; with respect to relative weight, total digestive tract represented 24.3% (p ≤ 0.055) with 12% inclusion of lignocellulose and small intestine 23.5% (p ≤ 0.005) in females. In the absolute and relative length of the small intestine, there was a statistical difference in the relative length with a result of 42.1% (p ≤ 0.005) in females; no significant variations were observed in the cecum, stomach and cecal pH. It is concluded that the levels of lignocellulose inclusion affect digestive parameters, in addition to increases in the length of the small intestine due to the percentage of fiber inclusion in the forage.